Effect of disinfection on adhesion of reline polymers - Gonçalves, Andréa [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha; Pavarina, Ana Claudia [UNESP] (Taylor & Francis Ltd, 2007)
Cylinders (3.5 x 5.0 mm) of the reline resins Kooliner (K), New Truliner (N), Tokuso Rebase Fast (T), and Ufi Gel Hard (U) were bonded to cylinders (20 x 20 mm) of the denture base resin Lucitone 550 (L), and samples were divided into two controls and four test groups (n = 8). Shear tests (0.5 mm/min) were performed after polymerization or immersion in water (37 degrees C) for 7 days (controls); two or seven cycles of disinfection by immersion in sodium perborate (50 degrees C/10 min) or microwave irradiation (650 W/6 min). Statistical analyses (alpha = 0.05) revealed that two cycles of microwave and chemical disinfection increased the mean bond strengths of materials T (9.08 to 12.93 MPa) and L (18.89 to 23.02 MPa). For resin L, seven cycles of chemical (15.72 MPa) and microwave (17.82 MPa) disinfection decreased the shear bond strength compared with the respective control (21.74 MPa). Resins U (13.12 MPa), K (8.44 MPa), and N (7.98 MPa) remained unaffected.
Keywords: bond strength; dental polymers; microwave irradiation